THE INFLUENCE OF E-COMMERCE ON THE COMPETITIVENESS OF UMKM USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) METHOD IN PAMULANG SUB-DISTRICT SOUTH TANGERANG CITY - Althaf Syah Abdali; Tituk Diah Widayantie (International Journal of Economy, Education and Entrepreneurship, 2023)
In the process of running a business or business, business actors must be aware of several factors that accompany the business or business activities, one of which is competitiveness. In this study, examining the effect of E-commerce on the competitiveness of MSMEs in the Pamulang sub-district with the Technology Acceptance Model (TAM) as a measure of technology acceptance that affects the competitiveness of MSMEs. The influence of E-commerce is analysed with several aspects of the Technology Acceptance Model, namely the ability to use a computer (X1), Aspects of usefulness (X2), Ease of use (X3), Aspects of Intention to use E-commerce (X4), and Aspects of actual use (X5). The data analysis technique begins with data compilation, data tabulation and finally the testing phase. This research uses quantitative methods. The value (R2) of 86.5% indicates that the variables (X1) - (X5) have an effect on the competitiveness of MSMEs and 13.5% are other factors. In conclusion, E-Commerce has an effect on the competitiveness of MSMEs